Diabetes research in Kenya from 2000 to 2020: A scoping review - Manyara, Anthony, Muchai; Musotsi, Protus (My University, 2023)
Background: The prevalence of diabetes is on the rise globally, with likely disproportionate increase in Sub-Saharan Africa. In Kenya, diabetes has been acknowledged as one of the top non-communicable diseases needing prevention and control. Research can contribute to diabetes prevention and control: however, the landscape of diabetes research in Kenya remains understudied. Methods: PubMed, MEDLINE, Scopus, PsycINFO, CINAHL, Google Scholar and ProQuest were searched for relevant articles. We included studies on humans, reporting on any type of diabetes, conducted in Kenya between 2000 to 2020. Results: From the search, 983 records were retrieved out of which 102 met the study inclusion criteria. Most studies were: conducted in Nairobi (38%) and between 2013-2020 (82%); non-public health, i.e., on diabetes control, (71%); cross-sectional (65%); descriptive (71%); facility-based (71%); and funded by organisations/institutions from high income countries (73%). Conclusion: Despite the recent increase in research outputs, there is still limited diabetes research being conducted in Kenya necessitating more research in the country and particularly outside Nairobi to inform prevention and control efforts. Specifically, more focus should be given to etiological and intervention studies (which use longitudinal and randomised controlled trial designs) community-based and public health research. Finally, increased local funding for diabetes research is required
Keywords: Africa; diabetes; Kenya; diabetes research